Case Report: Bradycardia in neonatal lupus: differential diagnosis between atrioventricular block and premature atrial contractions with block - Liu, Wei-Li; Peng, Ying-Hsuan (Frontiers in Pediatrics, 2024)
Neonatal lupus may be associated with severe cardiac conduction problems, including a high degree or complete atrioventricular (AV) block, necessitating immediate pacemaker implantation during the neonatal period. However, cardiac manifestations of neonatal lupus may extend beyond AV block. Our case presented a full-term female neonate, in whom fetal arrhythmia was noted and bradycardia with heart rates about 70-75 beats per minute was founded after birth. Neonatal lupus was diagnosed later due to positive maternal and neonatal anti-SSA/Ro antibody. High degree AV block was considered initially but bigeminy premature atrial contractions (PACs) with block was confirmed by detailed evaluation of electrocardiogram (ECG) which demonstrated not fixed PP interval and fixed RR interval. And atrial tachycardia (AT) developed at 23-day-old. The key point to differentiate from high degree AV block and PAC with block is the PP interval. The PP interval is fixed in high degree AV block and not fixed in PAC with block. Careful differential diagnosis is required in neonates with bradycardia because it may lead to very different management. Our case presents a good illustration to differentiate these arrhythmias. Besides, our case may be the first case of neonatal lupus with AT.